Measuring of Entrepreneurial Intention of University Students: Evidence from Students of Economic Sciences – University of Adrar - Kaloune, Djilali; Ayad, Salah (Finance and Business Economies Review, 2019)
This research aims to measure the entrepreneurial intention of the university students, and determines the impact of personal variables on the entrepreneurial intention. To achieve this goal, a model conceived showing the hypothetical relationship between the study variables, and a sample contains 120 students from the faculty of Economics is taken. In order to testing hypotheses, a descriptive statistical tool and analyse of variance were used. The main result of this study indicates that there is a real intention among student to create a small business, and the differences between students have no statistical significance on the entrepreneurial intention.